Emissions structure: a systemic analysis to Brazilian economy - 2003 and 2009 - Fernando Perobelli; Vinicius Vale (European Regional Science Association (ERSA), 2014)
In the recent period, there is an increase in the household income in Brazil. There is a positive impact upon consumption and welfare. On the other hand is important to verify the impact upon emissions derived from household consumption. The literature presents two approaches to analyze emissions. They are: account CO2 emissions based on the production principle and on the consumer principle. According to the consumer principle, the consumer is responsible for CO2 emissions from the production of energy, goods and services. In this case, the CO2 emissions are related to final use of goods and services even if they are imported from other countries. In order to reach the main aim of this paper we will use an input-output approach, specifically the extraction method. We use input-output matrix calibrated for 2003 and 2009 for the Brazilian economy considering 35 production sectors. We opened the household consumption into eight income categories. We closed the input-output model for household. This enables us to better understand the impact of each class of consumption upon the CO2 emissions.
Keywords: Q50; C67; 330; EMISSIONS; INPUT-OUTPUT